Identification and validation of single nucleotide polymorphisms as tools to detect hybridization and population structure in freshwater stingrays - Cruz, Vanessa P. [UNESP]; Vera, Manuel; Pardo, Belén G.; Taggart, John; Martinez, Paulino; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Wiley, 2017)
Single nucleotide polymorphism (SNP) markers were identified and validated for two stingrays species, Potamotrygon motoro and Potamotrygon falkneri, using double digest restriction-site associated DNA (ddRAD) reads using 454-Roche technology. A total of 226 774 reads (65.5 Mb) were obtained (mean read length 289 ± 183 bp) detecting a total of 5399 contigs (mean contig length: 396 ± 91 bp). Mining this data set, a panel of 143 in silico SNPs was selected. Eighty-two of these SNPs were successfully validated and 61 were polymorphic: 14 in P. falkneri, 21 in P. motoro, 3 in both species and 26 fixed for alternative variants in both species, thus being useful for population analyses and hybrid detection.
Keywords: conservation tools; genetic fish; hybridization; NGS techniques; Potamotrygon; SNPs